A key for the determination of European species of Eosentomon Berlese, 1909 (Protura, Eosentomata, Eosentomidae) - Shrubovych, Julia (Zookeys, 2018)
Abstract. European species of Eosentomon are examined. A taxonomic key to identification of 61 Eosentomon species is provided based on body chaetotaxy, shape, and position of sensilla on the foretarsus and shape of sensilla on the maxillary palps. Biogeographically, 13 of the known European Eosentomon species are known only from their type localities.